Learning of Science among Students at Risk of Dropping out (Sardo) Using Technology-Driven Intervention - Pañares, Mylene Amor Sayson; Ybanez, Reggie Sayson (Future Science / FSH-PH Publications, 2021)
The purpose of this study was to determine the efficacy of Technology-Driven Intervention in improving science learning among Alegria National High School students at risk of dropping out. This study focused on two groups of twenty (20) Grade 8 Students at Risk of Dropping Out. Ten SARDOs served as the control group and received work text intervention, while the other ten SARDOs received technology-driven intervention. Both groups performed POORLY in Science knowledge at the start of the experiment, according to the results. T-test results also revealed that both the work text intervention and the technology-driven intervention were effective in the learning of SARDOs. The mean gain scores of SARDOs that used technology-driven intervention, on the other hand, were significantly higher. The study concludes that a technology-based intervention is more effective than a traditional intervention for students at risk of dropping out.